Downtime on the Microgrid: Architecture, Electricity, and Smart City Islands - McCullough (MIT Press, 2020)
Monograph
fulltext
Keywords: Components, Circuits, Devices and Systems; Fields, Waves and Electromagnetics; Power, Energy and Industry Applications